A Transcendentalist Critique of Herman Hesse’s Siddhartha - Bibi, Saira; Ramzan, Muhammad; Muhammad, Naseer; Khan, Dr. Nijat Ullah (The journal of contemporary issues in business and government, 2021)
The paper is an attempt to find out the ways of achieving eternal peace, perfection, and recognizing self and God in Herman Hesse’s novel Siddhartha (2003) from the prospective of Transcendentalism. The main issue of the paper is to explore how far the elements of Transcendentalism flow through the text of the selected novel and how characters achieve their goal by recognizing self and individuality. Herman Hesse and Transcendentalists are well known for spiritual themes relating God, self, nature, and perfection. This qualitative study finds out that the novel is abundant in themes borrowed from Transcendentalism. The research in this way opens further avenues for analyzing the text through the perspectives of Transcendentalism.